2017
DOI: 10.1074/jbc.m117.802066
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of Gab1 and Gab2 adaptor proteins skew interleukin-4 (IL-4) signaling toward M2 macrophage-driven pulmonary fibrosis in mice

Abstract: M2-polarized macrophages, also known as alternatively activated macrophages, have long been associated with pulmonary fibrosis; however, the mechanism has not been fully defined. Gab1 and Gab2 proteins belong to the Gab family of adaptors and are integral components of the signal specificity in response to various extracellular stimuli. In this report, we found that levels of both Gab1 and Gab2 were elevated in M2-polarized macrophages isolated from bleomycin-induced fibrotic lungs. Gab1/2 deficiency in bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 74 publications
2
50
0
Order By: Relevance
“…Gab1 and Gab2 (Gab1/2) are widely expressed in various cell types, including immune cells such as T cells, and mast cells. A recent study demonstrated that the deficiency of either Gab1 or Gab2 resulted in impaired M2 polarization (53). Gab1 regulates IL-4-induced macrophage polarization by activating AKT signaling (53).…”
Section: Analysis Criteria Of In Vivo and In Vitro Signatures And Ovementioning
confidence: 99%
“…Gab1 and Gab2 (Gab1/2) are widely expressed in various cell types, including immune cells such as T cells, and mast cells. A recent study demonstrated that the deficiency of either Gab1 or Gab2 resulted in impaired M2 polarization (53). Gab1 regulates IL-4-induced macrophage polarization by activating AKT signaling (53).…”
Section: Analysis Criteria Of In Vivo and In Vitro Signatures And Ovementioning
confidence: 99%
“…Rather, STAT3 signaling is mediated, at least in part, by phosphorylated Gab2 at S623. Because of the ability to tether signaling molecules, Gab2 has been shown transmit signals to molecules such as STAT 43 . So far two phosphorylation sites on Gab2 have been implicated in STAT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that IL-4 is the major inducer for macrophage M2 program by activating its two major downstream signals, JAK1/STAT6 and PI3K/AKT [ 88 , 104 ]. Indeed, Guo et al reported that elevated Gab1 and Gab2 regulate IL-4-induced macrophage polarization in bleomycin-induced fibrotic lungs, with Gab1 positively regulating AKT signaling and Gab2 positively regulating STAT6 signaling [ 105 ]. Similarly, Kral et al noted that myeloid PTEN deficiency mice following bleomycin induction manifest sustained PI3K activation to enhance macrophage M2 program, leading to increased morbidity and decreased survival, although these mice exhibit impaired recruitment function [ 106 ].…”
Section: Alternatively Activated Macrophages (M2) and Ipfmentioning
confidence: 99%